The agencies of landscape in rural gentrification: Impressions from the wood, the village and the moortop. Issue 4 (7th July 2021) - Phillips, Martin; Smith, Darren; Brooking, Hannah; Duer, Mara
Abstract: This paper brings together research on rural gentrification with emerging work on lived landscapes that has emphasized the intertwining of the human and more‐than‐human with the performance of activities of everyday living and their affective significance. It draws on research examining rural gentrification in three contrasting landscapes, termed 'the wood', 'the village' and 'the moortop'. These landscapes connect to earlier studies of rural social change and gentrification in England, with 'the wood' and 'the village' being sites research by Ray Pahl and the 'moortop' one of the landscapes identified in Darren Smith and Deborah Phillips' examination of the role of representations of rurality in processes of rural gentrification. The paper draws on research that returned to the locations of this earlier research, and seeks to re‐examine arguments advanced by these studies about the formation of socially differentiated worlds and representations of rurality through a lived‐landscape perspective.